Peran Guru dan Sekolah dalam Pembelajaran IPAS Berbasis Deep Learning di Sekolah Dasar - Ananda Renie Aulia; Annisa Roihatul Jannah; Ahmad Rohman Bayhaqi (JURNAL ILMIAH NUSANTARA, 2026)
This study aims to describe the roles of teachers and schools in implementing deep learning-oriented science learning within the Merdeka Curriculum in elementary schools. This research employed a qualitative descriptive approach conducted through classroom observations, interviews with classroom teachers and school principals, and documentation. The study was carried out at a public elementary school in East Jakarta during November 2025. The findings indicate that teachers play a crucial role in designing learning through teaching modules aligned with learning outcomes, implementing active and project-based learning, and applying authentic assessments to support deep understanding. Schools support deep learning through policies, professional development programs, provision of facilities, and the creation of a conducive learning ecosystem. These findings imply that synergy between teachers and schools is essential to strengthen meaningful science learning and promote deep understanding among elementary students.